2010
DOI: 10.1590/s0006-87052010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Identificação e avaliação de rizobactérias isoladas de raízes de milho

Abstract: RESUMOEstudos sobre a atividade microbiológica que ocorre na rizosfera de diversos vegetais levaram ao descobrimento de grupos de microrganismos importantes para o desenvolvimento vegetal. Dentre eles estão as rizobactérias que são capazes de colonizar as raízes, estimulando-a diretamente ou beneficiando o crescimento e o desenvolvimento de diversas plantas. Estas bactérias são chamadas Rizobactérias Promotoras de Crescimento em Plantas (RPCP). Este trabalho teve o objetivo de isolar, identificar, testar a cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
1
12
0
10
Order By: Relevance
“…Pedrinho et al (2010), in a study on the activity of microorganisms in maize rhizosphere, observed phosphate solubilization and production of indole acetic acid (IAA) by bacteria of the genus Azospirillum. The increment of variables related to maize growth due to the isolated use of Azospirillum brasilense or combined use with N and/or other bacterial species has already been reported by Hungria et al (2010), Dartora et al (2013), Hahn et al (2013), Mazzuchelli et al (2014) and Marini et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Pedrinho et al (2010), in a study on the activity of microorganisms in maize rhizosphere, observed phosphate solubilization and production of indole acetic acid (IAA) by bacteria of the genus Azospirillum. The increment of variables related to maize growth due to the isolated use of Azospirillum brasilense or combined use with N and/or other bacterial species has already been reported by Hungria et al (2010), Dartora et al (2013), Hahn et al (2013), Mazzuchelli et al (2014) and Marini et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects of inoculation with H. seropedicae on the host plant, although not yet fully elucidated, can be attributed to biological fixation of atmospheric nitrogen (Urquiaga et al, 1992), phosphate solubilization (Pedrinho et al, 2010), synthesis of phytohormones (Radwan et al, 2004) and production of ACC deaminase (Rothballer et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For maize, the inoculation of the bacteria Azospirillum and Herbaspirillum brought positive results in the growth and development of plants (Baldani et al, 2009;Dotto et al, 2010;Pedrinho et al, 2010). However, there is little stability of the plant response to bacterization and the technology of diazotrophs needs to be adjusted to nonleguminous plants (Roesch, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lana et al (2012) report positive effect of inoculation with A. brasilense in the absence of N as top-dressing, with increment of 15% in maize yield; other studies also highlight the effect of maize growth promotion caused by other PGPB genera, such as: Sphingomonas spp. (Pedrinho et al, 2010), Burkholderia spp. (Alves et al, 2015), Herbaspirillum spp.…”
Section: Introductionmentioning
confidence: 99%